Historical postmortem studies on catatonia: close reading and analysis of Kahlbaum's cases and scientific texts between 1800 and 1900 - Hirjak, Dusan; Ams, Miriam; Gass, Peter; Kubera, Katharina Maria; Sambataro, Fabio; Foucher, Jack R.; Northoff, Georg; Wolf, Robert Christian (Schizophrenia research, 2024)
In the 19th century, postmortem brain examination played a central role in the search for the neurobiological origin of psychiatric and neurological disorders. During that time, psychiatrists, neurologists, and neuropathologists examined autopsied brains from catatonic patients and postulated that catatonia is an organic brain disease. In line with this development, human postmortem studies of the 19th century became increasingly important in the conception of catatonia and might be seen as precursors of modern neuroscience. In this report, we closely examined autopsy reports of eleven catatonia patients of Karl Ludwig Kahlbaum. Further, we performed a close reading and analysis of previously (systematically) identified historical German and English texts between 1800 and 1900 for autopsy reports of catatonia patients. Two main findings emerged: (i) Kahlbaum's most important finding in catatonia patients was the opacity of the arachnoid; (ii) historical human postmortem studies of catatonia patients postulated a number of neuroanatomical abnormalities such as cerebral enlargement or atrophy, anemia, inflammation, suppuration, serous effusion, or dropsy as well as alterations of brain blood vessels such as rupture, distension or ossification in the pathogenesis of catatonia. However, the exact localization has often been missing or inaccurate, probably due to the lack of standardized subdivision/nomenclature of the respective brain areas. Nevertheless, Kahlbaum's 11 autopsy reports and the identified neuropathological studies between 1800 and 1900 made important discoveries, which still have the potential to inform and bolster modern neuroscientific research in catatonia.